Case Report: Unique immunotherapy response in a patient with metachronous colorectal cancer not associated with Lynch Syndrome - Krishnamurthy, Nithya; Cohen, Deirdre (Frontiers in Oncology, 2025)
Metachronous colorectal cancers (mCRC) occur in 3.4% of cases within 10 years of initial diagnosis, with risks elevated in hereditary conditions like Lynch syndrome. We report a case of a 78-year-old male with a history of left-sided colon cancer (pT2N0M) resected in 2015 without adjuvant therapy, presenting in 2024 with a proximal ascending colon mass. The initial tumor was poorly differentiated adenocarcinoma, MLH1 and PMS2-deficient, and exhibited BRAF overexpression. The metachronous tumor was a moderately differentiated adenocarcinoma with a tumor mutational burden of 58 mutations/megabase and a BRAF V600E mutation. At the time of the second colon cancer diagnosis, germline testing was negative for Lynch syndrome, and Pembrolizumab was initiated due to the mismatch repair-deficient (MMR) status. The patient had a remarkable response to immunotherapy, with complete resolution of the colonic tumor on subsequent colonoscopies 3 and 6 months after initiation of immunotherapy with single-agent Pembrolizumab. Despite the absence of familial predisposition, microsatellite instability high (MSI-H) and MMR-deficient tumors confer increased mCRC risk. Surveillance remains critical post-resection, particularly in patients with MSI-H and MMR-deficient tumors, even without Lynch syndrome. Further studies are needed to elucidate mCRC risks and outcomes in non-Lynch syndrome, MSI-H colorectal cancer cohorts.